Faktor-Faktor yang Mempengaruhi Tingkat Pengungkapan Risiko Perusahaan pada Industri Perbankan di Indonesia - Harri Baskoro Adiyanto (Universitas Peradaban, 2018)
This research wants to examine the effects of Bank Size (CSIZE), Profitability (PROFIT), Public Shares Ownership (ISSUE), Total Number of the Board of Commissioner (BSIZE), Total Meeting of the Board of Commissioner (RPTDEKOM), and Member of Commissioner with background from Banking Supervisory Institution (BIDEKOM) to Corporate Risk Disclosure (CRD). This research analysis method uses multiple linear regression analysis models. The result of this research shows that the data has fulfilled the classical assumption, such as there is no multicollinearity and heteroscedasticity also data has distributed normally. From the regression analysis, found that partially Bank Size, Profitability and Member of Commissioner with Background from Banking Supervisory Institution variable, are significant to Corporate Risk Disclosure, while Public Share Ownership, Total Number of the Board of Commissioner and Total Meeting of the Board of Commissioner are not significant to Corporate Risk Disclosure.